Ancient Jewish Diaspora : Essays on Hellenism - Bloch, René (Supplements to the Journal for the Study of Judaism, 2022)
The fifteen papers collected in this volume all tackle the complex cultures of Jewish Hellenism. The book covers a wide range of topics, divided into four clusters: Moses and Exodus, Places and Ruins, Theatre and Myth, Antisemitism and Reception.